Sólidos micro-mesoestruturados tipo zeólita ZSM-5/peneira molecular MCM-41 - síntese e estudo de propriedades - Gonçalves, Marli Lansoni (Universidade Federal de São Carlos, 2006)
In the transformation of bulky molecules, the necessity of catalysts that allow the diffusion to and from the active sites located in the interior of the porous system has become of higher interest. The restriction for the diffusion of this type of molecule in zeolites has led the community to study routes that can make possible to obtain solids that allow the diffusion in mesoporous and simultaneously possess the intrinsic properties of microporous zeolites. In this context, the objective of this work was the synthesis of micro-mesostructured Zeolite ZSM-5/MCM-41 Molecular Sieve type solids. These solids were prepared under hydrothermal conditions in two stages. Initially was prepared a gel of ZSM-5 seeds, which was subsequently crystallized in the presence of cetyltrimetylammonium bromide (CTABr), used as structure directing agent in the synthesis of the MCM-41. The influence of the Si/Al ratio in the seeding gel and the effect of both the time and temperature used in the preparation of such gel and during crystallization were evaluated. X-ray diffraction in the low and wide angle region, nitrogen adsorption/desorption, FTIR spectroscopy and scanning and transmission electron microscopy data evidenced the formation of micro-mesostructured ZSM-5/MCM-41 materials. It is suggested that the formation of the microporous structure occurs by an intraparticle "solid-to-solid" process through the transformation of the walls of the mesoporous into crystalline structure. During the growth of the crystals, the surfactant micelles are dislocated, causing loss of the symmetry of the mesoporous arrangement. However, the micelles remain unchanged in a random array, generating after calcination irregularly arranged mesoporous, but possessing uniform diameters. The cristallinity of the formed ZSM-5 crystals, the volume of the mesoporous and the specific surface area of the final solid were influenced by the Si/Al ratio in the seeding gel and by the time and temperature used in the aging and during the stage of mesostructuration/crystallization. The optimization of this set of variables will allow the control of the ratio between the obtained microporous and mesoporous phases, thus making possible the preparation of tailor-made adsorbents and catalysts for the separation and transformation of bulky molecules.
Keywords: Catálise; Compósitos; Zeólita; ZSM-5; Peneira molecular; ENGENHARIAS::ENGENHARIA QUIMICA